Marketing Strategy In Surabaya City Archieves And Library - Fahriyah, Fahriyah (Record and Library Journal, 2015)
Successfull organizations are able to design and manage their information and the supporting technologies as a strategic weapon as well as an information utility. This requires information to be readily available on an asneeded basis to staff, management, customers, suppliers and other stakeholders. Surabaya City Archives and Libraries use the strategic marketing to disseminate information resources at their disposal. The purpose of this research is to know, how the marketing of library in Surabaya City Archives and Libraries. The research method uses literature study with data collection techniques derived from interviews and literature study. Fordata analysis, the results were processed and analyzed interviews with marketing theory using some of the literature from books, journals and the results of previous studies. Surabaya city Library and Archive wasfoundsome elementsin the Marketing Mix or library marketing strategy that has beenappliedin thelibrary since 2007. Adjustment of marketing strategy or concept 7P Marketing Mix are Product, Price, Promotion, Place, People, Process and Physical Evidencein the library have increased performance results Surabaya City Archives and Libraries since 2007 until now.